Ground-based detection of an extended helium atmosphere in the Saturn-mass exoplanet WASP-69b - Nortmann, Lisa; Yan, Fei; Henning, Thomas; Quirrenbach, Andreas (Science, 2018)
Helium escaping from hot gas giants. Many gas giant exoplanets orbit so close to their host star that they are heated to high temperatures, causing atmospheric gases to escape. Gas giant atmospheres are mostly hydrogen and helium, which are difficult to observe. Two papers have now observed escaping helium in the near-infrared (see the Perspective by Brogi). Allart et al. observed helium in a Neptune-mass exoplanet and performed detailed simulations of its atmosphere, which put constraints on the escape rate. Nortmann et al. found that helium is escaping a Saturn-mass planet, trailing behind it in its orbit. They combined this with observations of several other exoplanets to show that atmospheres are being lost more quickly by exoplanets that are more strongly heated. Science, this issue p. 1384, p. 1388; see also p. 1360. Hot gas giant exoplanets can lose part of their atmosphere due to strong stellar irradiation, and these losses can affect their physical and chemical evolution. Studies of atmospheric escape from exoplanets have mostly relied on space-based observations of the hydrogen Lyman-α line in the far ultraviolet region, which is strongly affected by interstellar absorption. Using ground-based high-resolution spectroscopy, we detected excess absorption in the helium triplet at 1083 nanometers during the transit of the Saturn-mass exoplanet WASP-69b, at a signal-to-noise ratio of 18. We measured line blueshifts of several kilometers per second and posttransit absorption, which we interpret as the escape of part of the atmosphere trailing behind the planet in comet-like form. Observations of helium show that the atmosphere of a hot Saturn-mass exoplanet is escaping and trailing behind the planet. Observations of helium show that the atmosphere of a hot Saturn-mass exoplanet is escaping and trailing behind the planet.
Gesehen am 16.10.2020